Sustainable nanocomposite porous absorbent and membrane sieves: Definition, classification, history, properties, synthesis, applications, and future prospects. Issue 2 (April 2023) - Ahmad, Sameer; Siddiqi, Weqar Ahmad; Ahmad, Sharif
Abstract: The everlasting need for safe drinking water, increasing maintenance costs, consumption of energy, and depletion of natural reserves have forced environmentalists and technologists to develop efficient techniques and suitable devices, which help in meeting global challenges. Therefore, the development of cost-effective sustainable porous polymer composite-based adsorbent and membrane sieves, and their use in wastewater treatment and other applications, have enormously attracted the interest of industrialists and researchers. The scalability, porosity, tunable surface chemistry, low environmental footprints, and functionalization of porous structures of composite adsorbent and membrane sieves have further enhanced the scope of their potential application in the field of wastewater and other environmental remediation. However, to achieve a deep understanding of their properties, processing, and applications a comprehensive exhaustive literature survey was conducted to report their brief history, classifications, bulk structural characteristics, designing strategies, and principles. The literature related to the construction of various advanced polymer sieves and other aspects of nanocomposite porous adsorbents and membrane sieves has also been discussed. In addition, the chemistry and mechanism involved in molecular separation through various polymer sieves are further reported. The strength of the present review is an attempt to cover the deep insights on sustainable porous adsorbent and membrane sieves, which has not been discussed earlier. The future scopes in relevance of the adsorbent and membrane sieves have also been covered. Graphical Abstract: ga1 Highlights: This review covers the different porous adsorbent and membrane sieves. Conventional to sustainable advanced sieves materials are reported. Different types of sieves classified based on their pore sizes. Bulk structural properties and synthesis routes of different sieves are covered. Chemistry and mechanism of sieves covered for wastewater and other applications.